Mobile Computing Technology with Mobile App Based Human Interference: - (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In a food ordering process, typically, multiple procedures are used to order the food in the restaurant where the client first browses the menu based on paper and then tells the waiter about the goods he has requested. Normally, before you start the operation, the consumer has to be seated. An alternative solution in respect of consumers is a mobile -based food pre-order framework, in which customers may build the order before joining the restaurant. Smartphone customer. The saved order may be checked by tapping the smart phone if the customer enters the restaurant. The list of the preordered goods picked is shown on the kitchen screen and the order slip is printed for further processing until verified. This approach helps you to pick a pre-order transaction type for consumers quickly and conveniently.